Consumer animosity, economic hardship, and normative influence: How do they affect consumers' purchase intention? - Huang, Yu‐An; Phau, Ian; Lin, Chad (European journal of marketing, 2010)
Purpose - This paper aims to examine the concept of "consumer animosity", model its antecedents, and assess its influence on intention to purchase. Design/methodology/approach - Survey questionnaires were distributed by a quasi-random sample of school pupils across Taiwan to an adult member of their household, for completion and return. A return rate of 70 percent yielded 456 usable questionnaires, the data from which were analysed by the LISREL structural equation modelling software. Findings - The results suggest that perceived personal economic hardship and the normative influence of members of a consumers' reference group have a positive impact on the phenomenon of consumer animosity, which in turn negatively affects the intentions of consumers in Taiwan to purchase products originating in mainland China and Japan. Contradicting previous studies, consumer animosity was found to be dependent on judgments of product quality. Research limitations/implications - The research model was built from data collected by non-probability sampling in a single country. There was no evidence of sampling bias, but future studies would benefit from inclusion of more independent variables and a wider geographical scope. Practical implications - The findings contain many practical lessons for planners of export marketing strategy. Originality/value - Two existing theories of social behaviour are integrated with the concept of consumer animosity to explain consumption choices in an international context. [PUBLICATION ABSTRACT]